mGlu receptors in endocrine organs - Durand, Daniela Elizabeth (2011)
Metabotropic glutamate (mGlu) receptors in the central nervous system are known to be essential for neuroplasticity associated with normal brain functions and are also critically involved in various neurological and psychiatric disorders. A recent surge of publications supports the presence, importance, and functionality of mGlu receptors outside the central nervous system with a unique distribution within various tissues. Group I, II, and III mGlu receptors are found in a wide range of peripheral organs including parts of the peripheral nervous system and nonneural organs such as hypophysis, pancreas, adrenal medulla, and the reproductive system. The distinct distribution of mGlu receptors in peripheral tissues is discussed in terms of possible functional endocrine implications.